Steels From Materials Science to Structural Engineering - Sha, Wei (Springer London : Imprint: Springer, 2013)
Steels and computer-based modelling are fast growing fields in materials science as well as structural engineering, demonstrated by the large amount of recent literature. Steels: From Materials Science to Structural Engineering combines steels research and model development, including the application of modelling techniques in steels.  The latest research includes structural engineering modelling, and novel, prototype alloy steels such as heat-resistant steel, nitride-strengthened ferritic/martensitic steel and low nickel maraging steel.  Researchers studying steels will find the topics vital to their work.  Materials experts will be able to learn about steels used in structural engineering as well as modelling and apply this increasingly important technique in their steel materials research and development. .